Un fac-similé, le choix pour Altamira - José Antonio Lasheras Corruchaga; Carmen de las Heras (In Situ, 2012)
The Néogrotte is a reproduction of the Altamira cave in its original state, and not in the way it has come down to us. In its shape and dimensions, it recreates the natural architecture of the cave and its underground area as it was in the Upper Paleolithic era, 14,000 years ago. Its creation represents a major effort in terms of geological and archaeological research and the development of technological application and advanced three-dimensional restitution. The scientific knowledge obtained by the project is made available to the museum's visitors.